Anisotropic Growth and Scanning Tunneling Microscopy Identification of Ultrathin Even‐Layered PdSe2 Ribbons. Issue 45 (23rd September 2019) - Jiang, Shaolong; Xie, Chunyu; Gu, Yue; Zhang, Qinghua; Wu, Xianxin; Sun, Yilin; Li, Wei; Shi, Yuping; Zhao, Liyun; Pan, Shuangyuan; Yang, Pengfei; Huan, Yahuan; et al.
Abstract: Palladium diselenide (PdSe2 ) is an emerging 2D layered material with anisotropic optical/electrical properties, extra‐high carrier mobility, excellent air stability, etc. So far, ultrathin PdSe2 is mainly achieved via mechanical exfoliation from its bulk counterpart, and the direct synthesis is still challenging. Herein, the synthesis of ultrathin 2D PdSe2 on conductive Au foil substrates via a facile chemical vapor deposition route is reported. Intriguingly, an anisotropic growth behavior is detected from the evolution of ribboned flakes with large length/width ratios, which is well explained from the orthorhombic symmetry of PdSe2 . A unique even‐layered growth mode from 2 to 20 layers is also confirmed by the perfect combination of onsite scanning tunneling microscopy characterizations, through deliberately scratching the flake edge to expose both even and odd layers. This even‐layered, ribboned 2D material is expected to serve as a perfect platform for exploring unique physical properties, and for developing high‐performance electronic and optoelectronic devices. Abstract : Ultrathin 2D PdSe2 is synthesized on novel Au foil substrates via a facile chemical vapor deposition route. An anisotropic growth behavior is detected from the evolution of ribboned flakes, which arises from the orthorhombic symmetry of PdSe2 and the unique metallic substrate of Au. A unique even‐layered growth mode is also confirmed by onsite scanning tunneling microscopy characterizations.